Lessons from the Field: Integrated survey methodologies for neglected tropical diseases. (10th December 2020) - Harding-Esch, Emma M; Brady, Molly A; Angeles, Cristiam A Carey; Fleming, Fiona M; Martin, Diana L; McPherson, Scott; Hurtado, Hollman Miller; Nesemann, John M; Nwobi, Benjamin C; Scholte, Ronaldo G C; Taleo, Fasihah; Talero, Sandra Liliana; et al.
Abstract: The 2021–2030 Neglected Tropical Diseases road map calls for intensified cross-cutting approaches. By moving away from vertical programming, the integration of platforms and intervention delivery aims to improve efficiency, cost-effectiveness and programme coverage. Drawing on the direct experiences of the authors, this article outlines key elements for successful integrated surveys, the challenges encountered, as well as future opportunities and threats to such surveys. There are multiple advantages. Careful planning should ensure that integration does not result in a process that is less efficient, more expensive or that generates data driving less reliable decisions than conducting multiple disease-specific surveys.